2005
DOI: 10.1111/j.1365-313x.2005.02578.x
|View full text |Cite
|
Sign up to set email alerts
|

A pathogen‐inducible patatin‐like lipid acyl hydrolase facilitates fungal and bacterial host colonization in Arabidopsis

Abstract: SummaryGenes and proteins related to patatin, the major storage protein of potato tubers, have been identified in many plant species and shown to be induced by a variety of environmental stresses. The Arabidopsis patatin-like gene family (PLPs) comprises nine members, two of which (PLP2 and PLP7) are strongly induced in leaves challenged with fungal and bacterial pathogens. Here we show that accumulation of PLP2 protein in response to Botrytis cinerea or Pseudomonas syringae pv. tomato (avrRpt2) is dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 69 publications
(90 reference statements)
5
139
0
2
Order By: Relevance
“…In contrast, loss-ofAtWRKY70 function resulted in enhanced susceptibility to E. cichoracearum and B. cinerea (AbuQamar et al 2006). Moreover, recent studies showed that necrotrophs deliberately trigger HR in the host, which subsequently leads to cell death and necrosis and hence might be a strategy used by these pathogens to initiate colonization of host tissue (Govrin and Levine 2000;La Camera et al 2005). The fact that AtWRKY70 expression is regulated both by defense-and senescence-associated signals acting in a coordinated manner indicates that AtWRKY70 function may be required to integrate signals that link both pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, loss-ofAtWRKY70 function resulted in enhanced susceptibility to E. cichoracearum and B. cinerea (AbuQamar et al 2006). Moreover, recent studies showed that necrotrophs deliberately trigger HR in the host, which subsequently leads to cell death and necrosis and hence might be a strategy used by these pathogens to initiate colonization of host tissue (Govrin and Levine 2000;La Camera et al 2005). The fact that AtWRKY70 expression is regulated both by defense-and senescence-associated signals acting in a coordinated manner indicates that AtWRKY70 function may be required to integrate signals that link both pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of theses proteins are patatinrelated plant PLAs (34)(35)(36)(37). Interestingly, AtPLP2 is a plant susceptibility factor during fungal and bacterial infection (37). By contrast, other PLA 2 s promote cell death associated with defense and development (34)(35)(36)38).…”
Section: Discussionmentioning
confidence: 99%
“…A number of PLA 2 enzymes have been linked to plant defense signaling (33). The majority of theses proteins are patatinrelated plant PLAs (34)(35)(36)(37). Interestingly, AtPLP2 is a plant susceptibility factor during fungal and bacterial infection (37).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, proteins with phospholipase A 2 activity (PLP2a/pPLA-II␣ and SOBER1) increased significantly in PM fractions during ETI. PLP2a/pPLA-II␣ has diverse lipid substrates in vitro and has been shown to accumulate during ETI and positively regulate cell death (41). In contrast, SOBER1 activity suppresses phosphatidic acid accumulation during ETI and represses HR in response to the effector AvrBsT (63).…”
Section: Fig 3 Go Biological Process Over-representation In Up-regumentioning
confidence: 99%